Typhoid Incidence and Infant Mortality across Nigerian Regions, 2015–2024: Descriptive Trends and Association Tests: English - Ajao, Olutunde Michael; Ayenigba , Alfred Ayo (CV. ARGA FARMA, 2026)
This study examines regional disparities in typhoid fever incidence and infant mortality across Nigeria from 2015 to 2024.Retrospective ecological study. Nigeria, covering the period 2015–2024. Secondary data were obtained from annual reports of the Nigeria Centre for Disease Control (NCDC) and the National Population Commission (NPC). Nigeria’s six geopolitical zones were aggregated into five macro-regions (Central, North, East, South, and West). Typhoid incidence was measured as cases per 100,000 population, while infant mortality was expressed as deaths per 1,000 live births. Descriptive statistics, Spearman correlation, fixed-effects panel regression, and one-way ANOVA were employed. The West region recorded the highest average typhoid incidence and infant mortality over the study period. Strong positive correlations between typhoid incidence and infant mortality were observed in the West (ρ = 0.89, p < 0.001) and South (ρ = 0.82, p = 0.023). One-way ANOVA confirmed significant regional differences (F = 8.64, p = 0.002), with post hoc analysis indicating that disparities were primarily driven by the West region. Substantial regional inequities persist in typhoid burden and infant mortality in Nigeria. Targeted, region-specific interventions focusing on water, sanitation, vaccination, and maternal–child health services are essential for reducing preventable infant deaths.